1995
DOI: 10.1111/j.1398-9995.1995.tb01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Melon sensitivity shares allergens with Plantago and grass pollens

Abstract: Possible associations between allergy to pollen and that to food allergens were studied in 262 patients sensitized to pollen. Forty-four patients (16.7%) showed some allergic symptoms after testing with fruits and vegetables, melon being the food most frequently involved (24 patients), followed by sunflower seed (12 patients). Skin testing was done by the prick method with natural fruit or vegetable, and also with commercial food extracts. We found in our region that the distribution of sensitivity to pollens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Several studies on melon allergy were carried out with different series of patients since its first description in 1970 [3]. Melon allergy is usually associated with hypersensitivity to pollens and other plant foods, OAS being its most common clinical manifestation [1, 2, 4–8]. In fact, only a low proportion of allergic subjects to melon show monosensitization or severe systemic reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies on melon allergy were carried out with different series of patients since its first description in 1970 [3]. Melon allergy is usually associated with hypersensitivity to pollens and other plant foods, OAS being its most common clinical manifestation [1, 2, 4–8]. In fact, only a low proportion of allergic subjects to melon show monosensitization or severe systemic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several works have confirmed the link between hypersensitivity to melon and allergy to different pollens, even in ragweed‐free areas [4]. Oral allergy syndrome (OAS) is recognized as the most common clinical manifestation of melon allergy [1, 2, 5–7]. Moreover, cross‐reactions of melon with other fruits [1, 4, 7, 8] and with latex [9] have been also reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), such as soybean, tomato, latex, rice, barley, alnus glutinosa, etc., that have structural homology to cucumisin (cucumisin‐like proteases) suggests its widespread and ubiquitous occurrence in plants. Additionally, to the best of our knowledge several authors have found an association between allergy to melon and latex [35] or melon and tomato [36], but the protein responsible for such cross‐reacitvity has not been evaluated, and it could be linked to cross‐reactivity to cucumisin‐like proteases from unrelated vegetables. Carbohydrate cross‐reactive determinant (CCD) should be bear in mind on evaluating this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies addressing the cross reactivity of IgE antibodies to conservative plant allergens have shown that profilins account for some of the fruit-fruit [5], fruit-plant pollen [6], and latex-food syndromes [7]. For example, it seems profilins are involved in the celery-mugwort-spice syndrome and cross-reactivity between ragweed pollen and cucurbitaceous family [8,9]. …”
Section: Introductionmentioning
confidence: 99%